Observations of a midlatitude squall line boundary layer wake - Hamilton, Paul J., author; Johnson, Richard H. (Richard Harlan), author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1987)
Mesoscale pressure perturbations frequently observed with mesoscale convective systems (MCS) are examined with special emphasis on the characteristics, structure, lifecycle and driving mechanism of the "wake depression" found in the wake region of the convection. A severe squall line which traversed the OK PRE-STORM surface and upper air mesonetwork on 10-11 June 1985 is the focus of this observational study. Extensive surface, upper air and digitized radar data collected during the OK PRE-STORM field experiment were used for analysis. Various mesoanalyses of this squall line at the surface and aloft have allowed for intensive examination of three pressure features observed with this squall line: the mesohigh, wake depression and pre-squall mesolow. Their relationship to and interaction with other meteorological parameters such as precipitation, temperature, potential temperature and moisture are explored. Furthermore, the mesoscale system-relative "jets" observed with midlatitude squall lines are examined for their possible influence on the pressure field. The mesohigh develops quickly during the early growth of the squall line and precedes the wake depression by several hours. The predominant mesohigh is linked to the formation of a large cold pool which developed as a result of widespread hail and intense rainfall from a supercell ahead of the young squall line. Analyses show that the wake depression is not a uniform, stagnant feature behind the mesohigh but has embedded small-scale features, a distinct lifecycle and can undergo rapid intensification. The wake depression also is related to some aspects of the squall line's precipitation pattern. The low consistently "hugs" the back edge of the stratiform precipitation and is observed to split into two separate lows as the convective line splits. Additionally, the wake depression is a hydrostatic response to a layer of warm, dry air (produced by subsidence) found just above the surface. It is suggested that the wake depression is in part a surface manifestation of forced subsidence by the descending rear inflow jet.
June 1987.
Keywords: Squall lines; Boundary layer (Meteorology)